2018
DOI: 10.1080/2162402x.2017.1408747
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Tumor-Expressed PD-1 promotes lung cancer growth

Abstract: Anti-PD-1 immunotherapy is the standard of care for treating many patients with non-small cell lung cancer (NSCLC), yet mechanisms of treatment failure are emerging. We present a case of NSCLC, who rapidly progressed during a trial (NCT02318771) combining palliative radiotherapy and pembrolizumab. Planned tumor biopsy demonstrated PD-1 expression by NSCLC cells. We validated this observation by detecting PD-1 transcript in lung cancer cells and by co-localizing PD-1 and lung cancer-specific markers in resected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
117
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(125 citation statements)
references
References 38 publications
8
117
0
Order By: Relevance
“…In pancreatic cancer, cell-intrinsic PD-1 promoted tumor growth through the Hippo signaling pathway outside the immune system [42]. However, Du et al found that cell-intrinsic PD-1 was presented in NSCLC as a tumor suppressor [43]. In our study, we found that patients with positive PD-1 expression in NPC tissues had shorter survival time, which is consistent with ndings in most malignancies.…”
Section: Discussionsupporting
confidence: 90%
“…In pancreatic cancer, cell-intrinsic PD-1 promoted tumor growth through the Hippo signaling pathway outside the immune system [42]. However, Du et al found that cell-intrinsic PD-1 was presented in NSCLC as a tumor suppressor [43]. In our study, we found that patients with positive PD-1 expression in NPC tissues had shorter survival time, which is consistent with ndings in most malignancies.…”
Section: Discussionsupporting
confidence: 90%
“…Yet, little is known about intrinsic PD‐1 pathway effects on tumour cells. Unlike its oncogenic functions in melanoma, blockade of PD‐1 promoted tumour cell proliferation in nonsmall cell lung cancer . Studies on the expression of PD‐L1 in cutaneous squamous cell carcinoma (cSCC) have increased .…”
mentioning
confidence: 99%
“…Multiple recent publications reported that cancer cells express not only PD-L1 but also PD-1 in tumour types such as melanoma, hepatocellular carcinoma, ovarian cancer, and NSCLC [69][70][71]. Until now, it had been believed that the PD-1 receptor could be expressed solely on haematopoietic cells [72].…”
Section: Pd-1 Intrinsic Signallingmentioning
confidence: 99%
“…Until now, it had been believed that the PD-1 receptor could be expressed solely on haematopoietic cells [72]. Strikingly, in their case report Du et al described rapid NSCLC progression (hyperprogression) in a patient treated with pembrolizumab [71]. Analysis of the tumour biopsy found NSCLC cells expressing the PD-1 receptor.…”
Section: Pd-1 Intrinsic Signallingmentioning
confidence: 99%
See 1 more Smart Citation